ANALISIS TERHADAP KONSTRUKSI KEADILAN DALAM PENETAPAN WARISAN ISLAM - Sri Hariati (Lembaga Penelitian dan Pengabdian kepada Masyarakat STIH Awang Long, 2026)
Islamic inheritance law is a part of Islamic law, based on the Qur’an and the commands of the Prophet Muhammad (peace be upon him). The mujtahids interpret these sources according to their own reasoning. In the pre-Islamic Jahiliyyah inheritance system, children and women were not granted inheritance rights. They did not receive spoils of war because they were considered weak and incapable of fighting. Inheritance was distributed only to adult male children, family members of the deceased, and even individuals who were not family members due to adoption or agreements. This is what distinguishes the Islamic inheritance system from the Jahiliyyah system, in accordance with Allah’s command, which grants property rights to family members. Therefore, it is important to understand and study Aristotle’s theory of distributive, corrective, and commutative justice. This research method is based on an analytical and constructive approach to the principle of proportional equality and the principle of balanced justice. The distribution of rights that should be granted to a person based on their obligations and abilities is known as proportional equality. Meanwhile, the principle of balanced justice in Islamic inheritance law regulates how inheritance is distributed between men and women.